Inter-societal security trilemma in Turkey: understanding the failure of the 2009 Kurdish Opening. (2nd January 2016) - Kardaş, Tuncay; Balci, Ali
ABSTRACT: This article examines the inter-societal security trilemma among political Islamists, Kurdish actors, and the state in Turkey with a special reference to the failures in the Kurdish Opening that was initiated in 2009. While the Kurdish question is undoubtedly a long-standing multi-state and multi-causal ethno-political phenomenon, this study is primarily concerned with the identity–security-politics nexus. It addresses the question of how the politics of identity and dynamics of contra-identity claims produce a persistent security dilemma among different political blocs in contemporary Turkey. Addressing this question helps to explain why the Turkish state has consistently failed to successfully tackle the Kurdish question, as was the case of the Kurdish Opening in 2009.